Children neglected: Where cumulative risk theory fails. (July 2015) - O'Hara, Mandy; Legano, Lori; Homel, Peter; Walker-Descartes, Ingrid; Rojas, Mary; Laraque, Danielle
Abstract: Neglected children, by far the majority of children maltreated, experience an environment most deficient in cognitive stimulation and language exchange. When physical abuse co-occurs with neglect, there is more stimulation through negative parent–child interaction, which may lead to better cognitive outcomes, contrary to Cumulative Risk Theory. The purpose of the current study was to assess whether children only neglected perform worse on cognitive tasks than children neglected and physically abused. Utilizing LONGSCAN archived data, 271 children only neglected and 101 children neglected and physically abused in the first four years of life were compared. The two groups were assessed at age 6 on the WPPSI-R vocabulary and block design subtests, correlates of cognitive intelligence. Regression analyses were performed, controlling for additional predictors of poor cognitive outcome, including socioeconomic variables and caregiver depression. Children only neglected scored significantly worse than children neglected and abused on the WPPSI-R vocabulary subtest ( p = 0.03). The groups did not differ on the block design subtest ( p = 0.4). This study shows that for neglected children, additional abuse may not additively accumulate risk when considering intelligence outcomes. Children experiencing only neglect may need to be referred for services that address cognitive development, with emphasis on the linguistic environment, in order to best support the developmental challenges of neglected children